Analysis of Teacher Ability in Learning Implementation Plan (RPP) in MIN 2, MTsN, and Man Kubu Raya 2013 Curriculum - Solihin Solihin; Sukino Sukino; Abdul Mukti (Arfannur, 2023)
The purpose of this study was to evaluate the readiness of the 2013 Curriculum Learning Implementation Plan (RPP) at MIN 2, MTSN, and MAN Kubu Raya by Akidah Akhlak teachers using a qualitative descriptive research methodology. In conducting research, a qualitative descriptive approach is used to assess a particular problem that arises and explain it by utilizing information obtained from written or oral findings relating to the subject under study. The results showed that the facultyâ€™s Akidah Akhlak teachers in compiling the 2013 Curriculum Implementation Plan (CIP) at MIN 2, MTSN, and MAN Kubu Raya were rated â€œvery goodâ€ based on three stages of observation conducted by researchers. The accuracy of the Learning Implementation Plan (RPP) prepared by each teacher was shown by an average achievement score of 83. 33% The first observation resulted in a score of 86%, while the second and third assessments resulted in a score of 78% and 86%, respectively. However, the acquisition of abilities does not always develop without being influenced by various conditions. The above achievements are the result of two different components, including internal and external elements.